Cousteaudinium aubryae (Dinophyceae, Cribroperidinioideae) from the lower to middle Miocene of the Pelotas Basin, southern Brazil: Morphology, biochronostratigraphy and paleobiogeography - Premaor, Eduardo; Ferreira, Elizabete P.; Guerstein, G. Raquel; Souza, Paulo A.; Arai, Mitsuru [UNESP] (Elsevier, 2023)
In this paper, we present a detailed morphological study of Cousteaudinium aubryae (de Verteuil and Norris, 1996) from Miocene deposits of the Pelotas Basin, southern Brazil. C. aubryae is a cyst of an autotrophic dinoflagellate with a great intraspecific morphological variability, evidenced by cavation type and degree, perforations and wall projections. Four morphotypes were identified, which are comparable with specimen records from other continents (e.g. North America and Europe). C. aubryae last occurred in the Pelotas Basin at levels chronocorrelated to the Helicosphaera ampliaperta calcareous nannofossil zone (N-570), suggesting age between Burdigalian and Langhian for the deposits of the Imbé and Cifreira formations. Integration of species records from different latitudes shows a paleobiogeographic distribution pattern predominantly in mid-latitudes, suggesting that C. aubryae was better adapted to non-tropical and no-polar climatic conditions during the early to mid Miocene.
Keywords: Brazil; Gonyaulacalean dinoflagellate cyst; Microplankton; Neogene; Pelotas Basin; Subfamily Cribroperidinioideae